"I got the power!": An exploration of contemporary fetishism. Issue 5 (11th November 2019) - Guelmami, Ziyed
Abstract : Purpose: This paper aims to discuss the concept of fetishism as an important but understudied kind of magical relationship to objects. Fetishism in the context of contemporary consumption is conceptualized as a multilayered construct underlining the attribution of an aura and magical power to a product to achieve personal goals. Design/methodology/approach: In total, 15 in-depth interviews were conducted to highlight contextual factors influencing the emergence of fetishism in contemporary consumption, to underline the instrumental and aspirational dimensions of fetishism and to provide a definition of contemporary product fetishism. Findings: The results show that fetishism appears as fragmented and unstable magical beliefs toward products related to a need to cope with uncertain and important aspirational situations. Originality/value: The paper provides a multidisciplinary approach of fetishism to provide insights regarding this phenomenon and its manifestations in the context of contemporary consumption.